Multi sensor system for classifying harumanis mango based on external and internal quality - Mohd Firdaus Ibrahim (School of Mechatronic Engineering, Universiti Malaysia Perlis, 2017)
The main objective of this thesis is to develop a system using machine vision and NIR spectrometer for classifying Harumanis mango based on its shape, mass and TSS. The objectives of this research are divided and addressed as below; to develop 3-Dimensional image acquisition technique for capturing image of the mango on a moving conveyor; to analyse the Harumanis mango features and classify the mango based on the shape and mass; to analyse the total soluble solid (TSS) of the mango using Near Infrared (NIR) spectrometer.